(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article analyzes the prospects of educational, scientific and technological cooperation between the Kyrgyz Republic and the countries of the Persian Gulf (Saudi Arabia, the United Arab Emirates, Qatar, Kuwait and Bahrain). The key areas of cooperation are considered - academic mobility, joint research projects, technology transfer and the development of the Islamic educational space. Special attention is paid to the role of educational diplomacy as a tool of “soft power” in the foreign policy of the Kyrgyz Republic and the Gulf states. It is noted that the growing participation of students and researchers of the Kyrgyz Republic in Arab and Islamic universities contributes not only to academic exchange, but also to the formation of a new layer of professional elite focused on the Islamic economy, engineering and digital technologies. At the same time, barriers are being identified - insufficient institutional coordination, linguistic and cultural differences, and limited joint research funds. A consistent conclusion is being formed that the sustainable development of educational cooperation requires strategic government support, the expansion of grant programs, the creation of joint centers for Islamic economics and innovation, as well as the participation of the Kyrgyz Republic in regional initiatives of the Persian Gulf countries in the field of science and technology.